The Identification of Motorcyclist Safety Risk among University Students in Yogyakarta, Indonesia - Kurnia, Fikrihadi; Samodro, Guntur (International Journal of Occupational Safety and Health, 2023)
Introduction: Traffic accidents are cases of concern both nationally and internationally. Their impact ranges from injuries to death. In Indonesia, traffic accidents are dominated by students who use motorcycles. With this in mind, this study is focused on identifying the driving attitudes that are responsible for traffic accidents among university students. Methods: The cross-sectional survey study was conducted from January 2023 to February 2023, located in the Special Region of Yogyakarta, Indonesia. Data was gathered using simple random sampling on 97 students based on experiences while driving such as safety attitude, frequencies on motorcycle inspections, and driving attitude. The next step is a comparison between results based on student experiences and risk assessment by experts. The expert assessment used two personnel of Police Resort from Yogyakarta and Purworejo, Indonesia. Results: Participants were divided into 81.4% men (N=79) and 18.6% women (N=18), with a mean age ± standard deviation of 21 ± 1.8 years. Awareness of safety attributes is demonstrated by the use of helmets by 92.78% of participants, and motorcycle inspections on rearview mirrors (85.57%), rims & tires (79.38%), and brakes (71.13%). In terms of road driving attitudes, students drive with fatigue (82.47%) and sick (61.86%), drive in bad weather (78.35%), and exceed the standard of speed (53.61%). The results of the risk assessment show that 7 variables have a high risk, namely helmet, inspection on the brake, driving in fatigued physical condition, driving in sick physical condition, using gadgets when driving, traffic sign violation, and overspeeding. Conclusion: Based on these results, it show that students' driving readiness is quite good with the attributes of vehicle safety and feasibility. This is shown by the use of helmets and break checks by students with the highest risk on the road. However, the need to be concerned is that the bad riding attitude includes physical health conditions, driving according to traffic safety standards, and paying attention to weather conditions. Improvements are needed especially by drivers to create safe and secure driving conditions.